Decisional support for young people who self-harm: protocol for a feasibility trial - Rowe, Sarah L.; French, Rebecca S.; Henderson, Claire; Ougrin, Dennis; Slade, Mike; Moran, Paul (BMJ Publishing Group Ltd, 2016)
Introduction: Self-harm is common in adolescents and it is the strongest predictor of suicide. Young people who self-harm are often unsure of how and where to get help. Decision aids (DA) have been shown to help with decisional conflict where there is uncertainty around different options. We have developed an online DA to support young people in help-seeking for self-harm. A feasibility trial will examine the acceptability of the online intervention, and the ability to recruit and follow-up participants within a school setting. Methods and Analysis: In this parallel arm, single blind feasibility trial, 60 participants aged 12-18 years who have self-harmed in the past 12 months, will be randomised to either: 1) a group receiving the online DA or 2) a control group receiving general information about feelings and emotions. Both groups will complete measures assessing decision-making and help-seeking behaviour. The school counsellor will be notified of any participants who have been randomised to ensure safeguarding for the young person. Participants in both groups will be followed up at 4-weeks and the measures will be repeated. Qualitative interviews will be conducted with a subset of participants to explore their views and experiences of the DA and of participation in the study. Ethics and Dissemination: Ethical approval was granted by King’s College London (KCL) College Research Ethics Committee. Results of this study will help to clarify if we can recruit and administer an online decisional support intervention within a school setting for young people who self-harm. The study will inform the design and implementation of a larger randomised controlled trial to test the effectiveness of the DA. Dissemination of the study findings will target publication in peer-reviewed journals of general and special interest. The funder will be sent a report outlining the major findings of the study.